Histomorphometry of the Duodenum of Ducks (Anas platyrhyncos) after Administration of Nanochitosan in Feed - Sunarno Sunarno; Solikhin Solikhin; Kustopo Budiraharjo (Biosaintifika: Journal of Biology & Biology Education, 2021)
Poultry farming business has several problems such as lack of availability on raw materials, expensive feed prices, and egg production that is not optimal. To overcome the problem of high feed prices and duck productivity, we need to add feed additives such as nanochitosan. Poultry farming business has several problems such as lack of availability on raw materials, expensive feed prices, and egg production that is not optimal. To overcome the problem of high feed prices and duck productivity, we need to add feed additives such as nanochitosan. This study aimed to analyze the effect of nanochithosan feed on the digestive function of the intestine tenue (duodenum) as indicated by histomorphometric changes in the duodenum of Tegal ducks (Anas platyrhyncos). Duodenal histomorphometry related to digestive function was measured, including changes in lumen diameter, villi height, epithelial cell thickness, and muscular layer thickness. This study used a completely randomized design consisting 5 treatments with 5 replications. The research treatments included P0 as control (basic feed without nanochitosan particle additives) and P1, P2, P3, and P4 (basic feed with the addition of nanochitosanwith the doses of 2.5; 5; 7.5; and 10 grams/kg feed respectively). The variables observed were lumen diameter, villi height, epithelial layer thickness, and duodenal muscle layer thickness. The research data were analyzed using the analysis of variance (ANOVA) with a 95% confidence level. The results showed that the addition of nanochitosan particles in the feed had a significant effect on the lumen diameter and thickness of the duodenal muscular layer (P0.05). Tegal ducks. The conclusion of this study is that nanochitosan feed additives with a concentration of 2.5-10% can improve digestive function and improve duodenal histomorphometry in the intestine tenue of Tegal ducks as indicated by an increase in lumen diameter, villi height, and the thickness of epithelial cell thickening, and muscular layer. The novelty from this study is the production and the used of nanochitosan as feed additive to repair histomorphometry of duodenum in intestine tenue of Tegal ducks. From this research, people gets benefit by knowing the use nanochitosan as feed additive to improve digestion performance and productivity of Tegal ducks.